\(\sum _{i=a}^{b-1} f(i)=\int_a^b f(x) \, dx+\frac{1}{2} (f(a)-f(b))+\frac{1}{12} \left(f'(b)-f'(a)\right)+\frac{1}{720} \left(f^{(3)}(a)-f^{(3)}(b)\right)+\frac{f^{(5)}(b)-f^{(5)}(a)}{30240}+\frac{f^{(7)}(a)-f^{(7)}(b)}{1209600}+\cdots\)
\(\sum_{i=a}^{b-1} f(i) = \int^b_a f(x)\,dx+\sum_{k=1}^p\frac{B_k}{k!}\left(f^{(k-1)}(b)-f^{(k-1)}(a)\right)+R\)
여기서
\(\left|R\right|\leq\frac{2}{(2\pi)^{2(p+1)}}\int_0^n\left|f^{(p)}(x)\right|\,dx\)
\(B_0=1\), \(B_1=-{1 \over 2}\), \(B_2={1\over 6}\), \(B_3=0\), \(B_4=-\frac{1}{30}\), \(B_5=0\), \(B_6=\frac{1}{42}\), \(B_8=-\frac{1}{30}\), \(B_{10}=\frac{5}{66}\), \(B_{12}=-\frac{691}{2730}\),\(B_{14}=\frac{7}{6}\) 는 베르누이 수
\(\frac{B_k}{k!}\) 는 \(\{1, -1/2, 1/12, 0, -1/720, 0, 1/30240, 0, -1/1209600, 0, 1/47900160, 0, -691/1307674368000, 0, 1/74724249600\}\)
\(\sum_{i=0}^{n-1} f(i) = \sum_{k=0}^p\frac{B_k}{k!}\left(f^{(k-1)}(n)-f^{(k-1)}(0)\right)+R\)
단, \(f^{(-1)}(x)=\int f(x)\,dx\) 라고 쓰자.